2012
DOI: 10.4329/wjr.v4.i4.151
|View full text |Cite
|
Sign up to set email alerts
|

Primary malignant fibrous histiocytoma of the abdominal cavity: CT findings and pathological correlation

Abstract: AIM:To study computed tomography (CT) �eatures of abdominal malignant fibrous histiocytoma (MFH) in various rare locations. METHODS:We retroprospectively identi�ied cases o� �FH involving the abdominal cavity. �articular attention was paid to details regarding imaging �eatures and histological types. RESULTS:The study population consisted o� seven men and one woman, with a mean age o� 52.5 years. Seven patients had some physical symptoms, while one was incidentally detected. The sites o� origin were liver (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 43 publications
(72 reference statements)
5
27
0
1
Order By: Relevance
“…However, not all inflammatory MFHs exhibit marked enhancement. Karki et al (21) reported 3 cases of inflammatory MFH, although only 1 case exhibited marked enhancement, whereas the remaining 2 cases exhibited mild enhancement. These different enhancement patterns may be the result of different tumor locations.…”
Section: Discussionmentioning
confidence: 99%
“…However, not all inflammatory MFHs exhibit marked enhancement. Karki et al (21) reported 3 cases of inflammatory MFH, although only 1 case exhibited marked enhancement, whereas the remaining 2 cases exhibited mild enhancement. These different enhancement patterns may be the result of different tumor locations.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant psoas syndrome is an uncommon condition caused by malignant infiltration of the psoas muscle and adjacent nerves and is characterized by (fixed) flexion deformity of the ipsilateral hip and proximal lumbosacral plexopathy, and this syndrome has been described in the case of UPS of the psoas muscle . The psoas muscle is a rare location for sarcomas, but soft tissue sarcomas originating from it should be managed like other high‐grade extremity and truncal sarcomas (with perioperative radiotherapy+/−chemotherapy) …”
Section: Introductionmentioning
confidence: 99%
“…They are divided into five different subgroups and the ones more commonly seen are pleomorphic and myxoid types, which tend to present higher grades, while the rarer giant cell, inflammatory and angiomatoid subtypes tend to present lower grades. 5 The etiology of MFH is not completely known; however, it is more common in patients who received radiotherapy, similar to other sarcomas. In addition, sunlight, chemical agents such as phenacetin, previous surgery, trauma and fracture, bone infarct, and tumors such as Hodgkin lymphoma and multiple melanoma are predisposing factors.…”
Section: Case Reportmentioning
confidence: 99%
“…Heterogeneous contrast enhancement might be seen in post-contrast images secondary to necrotic and hemorrhagic components. 5 Fluid-fluid levels may be seen secondary to hemorrhage in CT and MRI. Signal properties of hemorrhagic component in MRI vary according to the character of the blood products.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation